Komunikasi Lintas Budaya Studi Kasus: Perubahan Tradisi Maucok pada Acara Baralek di Nagari Koto Berapak Kecamatan Bayang Kabupaten Pesisir Selatan - Kevin Asraf Rafiyel; Alfalah Alfalah (INDO PUBLISHING, 2026)
The research aims to explore the causes of change in the maucok tradition at the baralek event in Nagari Koto Berapak, Bayang District, Pesisir Selatan Regency. The maucok tradition is a process of inviting people to the baralek event is held, and when it is held. Based on the maucok tradition , it is still carried out by minangkabau people in Nagari Koto Berapak, Bayang District, Pesisir Selatan Regency, but currently they still use gulo-gulo to invite people to the baralek event. From these changes, the role of niniak mamak and the traditional order in the nagari faded and the niniak mamak tried to change the changed traditional again by holding a meeting at the KAN (Nagari Traditional Office) with other traditional stakeholders regarding their disagreement with the change tradition . The results of this research show that this has a big impact on the Koto Berapak Nagarian customs and the interest between mamak and kamanakan in a korong (region) of a tribe. From example, the kamanakan’s lost/diminished trush in the mamak when communicating, looks like underestimating/underestimating the traditional order in the nagari. If there is no change in the kerapatan adat nagari and niniak mamak then the cultural traditions of Nagari Koto Berapak will simply disappear. This research uses qualitative research methods using socialchange theory. This data collection was carried out by means of interviews, observation, and also literature studies related to titles and analysis to create a framework for thinking.